A Cros Sectional Study on the Plateletcrit and Platelet Indices in Different Forms of Dengue Fever - Sadaqat Hussain, Unaiza Sharif, Abdul Kabeer Baig, Sehrish Raja, Muhammad Khurram, Saira Mahmood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dengue fever is a viral disease caused by four different serotypes of dengue viruses from DENV, transmitted mostly by the Aedes aegypti mosquito. The disease has history of many outbreaks mostly in tropic and sub-tropic countries, costing many lives annually, with millions in mild to complicated forms, bringing stress to health systems and economies of poor countries. Dengue epidemic occurred in Pakistan in 2010 with 257 deaths during the epidemic and prevalence of 16580 cases in Rawalpindi, repeated epidemic in 2015, 2017, 2018 and 2019 with higher prevalence. Objective: To determine the frequency of dengue hemorrhagic fever in patients of dengue fever and to compare mean platecrit and platelet indices in patients with or without dengue hemorrhagic fever due to dengue fever. Materials And Methods: The design of this study was an observational cross sectional study design. This study was conducted in the Department of Infectious Diseases, Holy Family Hospital, Rawalpindi and the duration of this study was 6 months after the approval of synopsis i.e 1st May 2021 to 30th Oct 2021. Patients fulfilling selection criteria were enrolled in the study from emergency of Department of Infectious Diseases, Holy Family Hospital Rawalpindi. Informed consent was taken. Then patients were evaluated and divided for severity score (annexure I). Reports were assessed for Platelet indices including platelet count, mean platelet volume, platelet distribution width (as per operational definition). All this information were recorded on proforma (attached). Results: Total 150 participants were enrolled in the study as per the inclusion criteria. Mean age in the study was 38.42+13.74 whereas there were 94 (62.7%) male and 56 (37.3%) female patients who were included in the study according to the inclusion criteria. Among 150 patients, 28 (18.7%) patients were presented with dengue hemorrhagic fever in patients of dengue fever. Mean Platecrit indices in patients with or without dengue hemorrhagic fever due to dengue fever in the study was 0.26+1.62 vs 0.08+0.02 (p-value 0.552) whereas mean platelet indices in patients with or without dengue hemorrhagic fever due to dengue fever in the study was 64.19+41.11 vs 78.10+32.74 (p-value 0.097). Practical Implication: To determine the frequency of dengue hemorrhagic fever in patients of dengue fever and to compare mean platecrit and platelet indices in patients with or without dengue hemorrhagic fever due to dengue fever Conclusion: The study concluded that different indices of platelets within different forms of dengue fever to assess the severity of the disease process may serve as an early indicator of disease progress and severity which will help to decide early intervention. Keywords: Dengue Fever, Hemorrhagic, Platelet, Indices, Serotypes, Epidemic, Participants